Factors Influencing Spatial and Temporal Characteristics of Organic Carbon Loading to Rivers From Sediment in Small Watersheds in Sugarcane Areas - Wu Zongmeng; Guo Hao; Li Yong; Chen Tingting; Zhou Xiaoqi; Yang Cuihong; Yang Jiangyi; Wang Xu; Huang Zhigang (Shuitu baochi tongbao)
[Objective] The spatial and temporal characteristics and influencing factors of soil organic carbon loss from sugarcane in a typical small watershed in the red soil area of Guangxi Zhuang Autonomous Region were determined, and the spatial and temporal changes of organic carbon from watershed sediment entering the river during different growth periods of sugarcane were analyzed in order to identify the factors influencing soil organic carbon loss under natural rainfall erosion. [Methods] The experimental area was located in the Nala sub-basin of the water source area of Kailan Reservoir at Fusui County, Chongzuo City, Guangxi Zhuang Autonomous Region. The watershed was divided into the lower sub-basin (S1) and the upper sub-basins (S2 and S3). The organic carbon of incoming sediment and vegetation cover were monitored during four growth periods (seedling, tillering, elongation, and maturity) of sugarcane using UAV technology and an automatic runoff sediment monitoring-sampling system. Pearson correlation analysis was used to determine the relationship between organic carbon of incoming sediment and influencing factors such as rainfall runoff, vegetation cover, and fertilizer application. [Results] ① The organic carbon load of sediment into the river during the seedling stage of sugarcane accounted for 61.1% of the total loss during the entire growing season, and this value was significantly greater than values observed in the other growing periods. Organic carbon load followed the order of seedling stage (5.1 kg/hm2) > maturity stage (1.6 kg/hm2) > elongation stage (1.4 kg/hm2) > tillering stage (0.3 kg/hm2); ② rainfall runoff and vegetation cover were significantly correlated with organic carbon loss from incoming sediment, explaining 45% and 54%, respectively, of the variation in organic carbon loss from incoming sediment during the growing season. Fertilizer application and soil bulk density were significantly correlated with organic carbon loss from incoming sediment in the watershed, explaining 79% and 36%, respectively, of the variation in organic carbon loss from incoming sediment during the growing season. [Conclusion] Studies have shown that organic carbon loss from watershed sediments is mainly influenced by rainfall runoff, vegetation cover, fertilizer application, and soil bulk density. In small watersheds in sugarcane areas, increasing vegetation cover to reduce surface runoff and regulating the timing of fertilizer application can play an important role in reducing soil organic carbon loss.